Clinical importance of serum heme oxygenase-1 measurement in patients with acute exacerbation of idiopathic pulmonary fibrosis triggered by coronavirus disease 2019. (2022) - Hara, Yu; Oshima, Yume; Tagami, Yoichi; Aoki, Ayako; Fujii, Hiroaki; Izawa, Ami; Seki, Kenichi; Kanai, Akinori; Yabe, Aya; Watanabe, Keisuke; Horita, Nobuyuki; Kobayashi, Nobuaki; et al.
Abstract: A 70-year-old man diagnosed with idiopathic pulmonary fibrosis (IPF) one year earlier developed progressive exertional dyspnea 3 weeks after onset of coronavirus disease 2019 (COVID-19). High-resolution computed tomography showed new extensive ground-glass opacities with rapidly progressive honeycombing. Although he was diagnosed with acute exacerbation (AE) of IPF triggered by COVID-19 and received methylprednisolone pulse therapy twice within one month, there was no improvement of oxygenation and lung involvement. Three months after COVID-19 onset, it was decided to provide best supportive care. An AE of IPF as a sequela of COVID-19, which is recognized as macrophage activation syndrome, is fatal, and in this case, the measurement of serum heme oxygenase-1, which is a macrophage activation biomarker involved in pulmonary cellular protection against oxidative stress, was useful for tracking disease activity.